IMPLEMENTASI ALAT PERAGA EDUKATIF (APE) BAGI PENINGKATAN MINAT ANAK DALAM PROSES PEMBELAJARAN DI RAUDHATUL ATFAL (RA) NURHIDAYAH PURWOSARI KECAMATAN PEMATANG BANDAR KABUPATEN SIMALUNGUN - Fadhilla Try Utami; Sartika Maharani Putri (Jurnal At-Tabayyun, 2023)
Early child education (paud) is the level of education prior to the basic education that is intended for children from birth to the age of six years made through educational stimulation to assist physical and spiritual growth and development in order for children to be prepared for further education. Learning that is an activity process to change the behavior of a subject learns to have factors influencing him. Of the many factors that influence, it can be classified horizontally into the second inner factor the subject is learning and the estern factor (from outside) the subject is learning. Among the internal factors and particularly psychological factors are some that influence learning, one of which is interest. The educational display is a learning medium that is sorely needed in the performance of the learning process. In early childhood child education the role of eductive visual models is crucial, educational displays for young children are powerful learning tools to further the child's interest in following learning. By, using the educational visual displays the learning process will continue more fun.